ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII PADA MATERI BENTUK ALJABAR DI MASA PANDEMI COVID-19 - Kesi Septripiyani; Chandra Novtiar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research was motivated by the low ability to understand mathematical concepts of algebra students during the Covid-19 pandemic. The purpose of this study was to describe the ability to understand the concepts of seventh grade students at MTs An naiim Bandung in learning mathematics in algebraic forms. The method used is descriptive qualitative research, data collection techniques used in this study are through tests, interviews and documentation. The analytical technique used in this study is a qualitative descriptive analysis technique. Based on the results of the analysis and discussion of research, namely the category based on the ability to understand mathematical concepts very high gets a percentage of 4.17%, the high category gets a presentation of 8.33%, the middle category gets a percentage of 25%, the low category gets a percentage of 30.83%, the very low category gets a percentage. the percentage is 33.3%. So it can be concluded from the results of the students' ability to understand mathematical concepts that students' abilities are still very low in algebraic form material.